Avaliação quantitativa do efeito da toxina botulínica tipo A em indivíduos com espasticidade do músculo bíceps braquial - Rezende, Andressa Rastrelo (2019)
Spasticity is a motor disorder characterized by increased muscle tone, dependent on the stretching velocity. This disorder affects around 12 milions of people worldwide and contribute to the increase of the incapacity of individuals, reducing their mobility and independence. The treatment can be realized through medications, physiotherapeutic or the application of botulinum toxin to the spastic muscles, na option that has been widely used in clinical practice. Botulinum toxin is a potente neuromuscular blocker, effective in the treatment of spasticity. Several studies were performed to verify the efficacy of toxin application in patients with spasticity, but the methods used for this verification were mostly subjective, such as the Ashworth Modified Scale. Thus, it is necessary to study new methods of assessing spasticity in order to be able to evaluate the real effect of the treatment. A new method that has been studied and has been applied in some studies is the Reflex Threshold Tonic Method (LRET). This measure represents the joint angle at which the joint muscles are being recruited. The aim of this study was to evaluate the effect of botulinum toxin type A on upper limbs of participants with spasticity. For this, two evaluations were used, one just prior to application and the other 21 days after application. Three parameters were evaluated: the Ashworth Modified Scale, the LRET method and the Elbow Range of Motion. The results were an evolution of the participants in relation to a more significant range of motion than those verified by the LRET method, referring to the neural dimensions of this disorder.